A communicative English course for children among the ages of 6- 12 using Howard Gardner’s multiple intelligences theory - Castaneda Escobar, Yanira Elizabeth; Pérez Flores, Bessy Aracely (2024)
The qualitative research study “A Communicative English Course Design for Children among the Ages of 6 - 12 Using Howard Gardner Multiple Intelligences Theory” at the Western Multidisciplinary Campus of the University of El Salvador builds on the necessity to design an English course syllabus and select an appropriate textbook to support EFL teachers in the English Extension Program. This qualitative study will help EFL teachers guide the instruction successfully in order to make children learn the target language through the application of Howard Gardner’s Theory of Multiple Intelligences.